MAX, lottery-type stocks, and the cross-section of stock returns: Evidence from the Chinese stock market - Hoang Van Hai (Cogent Economics & Finance, 2023)
This study empirically investigates a relationship between MAX and lottery-type stocks in the Chinese stock markets. We find that the lottery-type stocks, which are preferred for lottery demand of investors, are negatively priced in the Chinese market. Moreover, the MAX effect as a proxy for lottery stock is not strongly exhibited as the lottery behavior in the Chinese stock market. Our results show that the higher MAX stocks in the lowest price stocks are stronger than those in the highest price ones. This can explain why the MAX phenomenon of the Chinese market is different from that in the developed market regarding the candidate of the IVOL puzzle explanation.
Keywords: G11; G12; G17; 330; Chinese stock market; Idiosyncratic volatility puzzle; limits of arbitrage; Lottery-type stocks; MAX effect